2007
DOI: 10.1007/s00705-007-1062-6
|View full text |Cite
|
Sign up to set email alerts
|

Atypical status of bovine spongiform encephalopathy in Poland: a molecular typing study

Abstract: SummaryThe aim of this study was to analyze molecular features of protease-resistant prion protein (PrP res ) in Western blots of BSE cases diagnosed in Poland with respect to a possible atypical status. Confirmed cases were analyzed by Western blotting with several monoclonal antibodies directed at N-terminal and core epitopes of prion protein (PrP). Most cases showed the classical glycoprofile characterized by the dominance of the di-over the monoglycosylated PrP res band, yielding di-=mono-ratios well above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Recently, L-type BSE cases were detected in several countries, 13,14,16,18,19 and their characteristics were investigated. 16,20,30,31 It has been reported that the European L-type BSE has a distinct glycoform of PrP Sc that has relatively weaker PK resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, L-type BSE cases were detected in several countries, 13,14,16,18,19 and their characteristics were investigated. 16,20,30,31 It has been reported that the European L-type BSE has a distinct glycoform of PrP Sc that has relatively weaker PK resistance.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] In recent years, several cases of atypical neuropathological and molecular phenotypes of BSE (atypical BSE) have been reported in Japan, several European countries and North America. [13][14][15][16][17][18][19] Atypical BSE cases are temporally classified into two groups-L-type and H-type-according to the molecular size of the proteinase K (PK) digested non-glycosylated form of PrP Sc . 18 However, the precise definition of atypical BSE prions remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the L-type group already mentioned (see Sect. 3.3.2), which has been identified in France [28], Italy [47], Germany [42] and Poland [151], a second group termed H-type has been found. Its PrP res signature is characterized by protease-resistant fragments of an increased size and a different glycopattern as compared to BSE [27].…”
Section: Diversity Of Tse Strains In Cattlementioning
confidence: 92%
“…Scientific studies report information on the identification of L-BSE in France , Italy , Germany (Buschmann et al, 2006), Great Britain (Stack et al, 2013) and Poland (Polak et al, 2008). H-BSE has been reported in France , Great Britain (Terry et al, 2007), Germany (Buschmann et al, 2006), the Netherlands (Jacobs et al, 2007) and Sweden (Gavier-Widen et al, 2008).…”
Section: And Data Reported By Member States To the European Commissiomentioning
confidence: 99%